Exosomes populate the cerebrospinal fluid of preterm infants with post‐haemorrhagic hydrocephalus. Issue 73 (9th January 2019) - Spaull, Robert; McPherson, Bryony; Gialeli, Andriana; Clayton, Aled; Uney, James; Heep, Axel; Cordero‐Llana, Óscar
Abstract: Background: Preterm infants are at risk of germinal matrix haemorrhage‐intraventricular haemorrhage (GMH‐IVH) which leads to post‐haemorrhagic hydrocephalus (PHH) in 30% of infants; this is associated with moderate‐severe neurodevelopmental impairment and confers significant risk of cerebral palsy. There are however no predictive indicators of the severity or long‐term outcome after GMH‐IVH. In recent years, endosome‐derived extracellular vesicles (EVs) or exosomes have been isolated from biofluids and shown to mediate intercellular communication via selective enrichment in proteins and micro‐RNAs. Methods: This study aimed to isolate and characterise EVs from the cerebrospinal fluid (CSF) of 3 preterm infants with PHH using nanoparticle tracking analysis (NTA), transmission electron microscopy (TEM) with immunogold protein labelling, and micro‐RNA analysis. Results: NTA of unaltered CSF revealed a heterogeneous and dynamic population of EVs. Exosomal‐sized EVs were isolated by differential ultracentrifugation and TEM confirmed the presence of CD63 + and CD81 + exosomes. The micro‐RNAs miR‐9, miR‐17, miR‐26a, miR‐124 and miR‐1911 were detected within the exosome‐enriched fraction and profiled over time. Conclusion: This is the first reported characterisation of exosomes from the CSF of preterm infants with post‐haemorrhagic hydrocephalus.